2018
DOI: 10.1021/acsomega.7b01752
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Synthesis of Polydopamine Coated ZnFe2O4 Composites as Anode Materials for Lithium-Ion Batteries

Abstract: Metal oxides as anode materials for lithium storage suffer from poor cycling stability due to their conversion mechanisms. Here, we report an efficient biomimetic method to fabricate a conformal coating of conductive polymer on ZnFe2O4 nanoparticles, which shows outstanding electrochemical performance as anode material for lithium storage. Polydopamine (PDA) film, a bionic ionic permeable film, was successfully coated on the surfaces of ZnFe2O4 particles by the self-polymerization of dopamine in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…An example of these molecules is SiO 2 , which is used to coat ZnFe 2 O 4 MNPs due to its desirable properties such as biocompatibility, non-toxicity, and dispersity in H 2 O 20 . So far, ZnFe 2 O 4 MNPs has been combined with variety of natural and synthetic polymers such as Chitosan 21 , Tragacanth gum 20 , Poly(vinylidene fluoride) 22 , Polydopamine 23 , polystyrene 24 , polyaniline 25 , polypyrrole 26 , poly(o-phenylenediamine) 27 , polythiophene 28 , polyvinyl pyrrolidone 29 , Poly(m-phenylenediamine) 30 , poly methyl methacrylate 31 for different purposes. In addition, there are various reports of different polymers growing during the polymerization process on the surface of MNPs to preparation novel magnetic star polymers 7 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…An example of these molecules is SiO 2 , which is used to coat ZnFe 2 O 4 MNPs due to its desirable properties such as biocompatibility, non-toxicity, and dispersity in H 2 O 20 . So far, ZnFe 2 O 4 MNPs has been combined with variety of natural and synthetic polymers such as Chitosan 21 , Tragacanth gum 20 , Poly(vinylidene fluoride) 22 , Polydopamine 23 , polystyrene 24 , polyaniline 25 , polypyrrole 26 , poly(o-phenylenediamine) 27 , polythiophene 28 , polyvinyl pyrrolidone 29 , Poly(m-phenylenediamine) 30 , poly methyl methacrylate 31 for different purposes. In addition, there are various reports of different polymers growing during the polymerization process on the surface of MNPs to preparation novel magnetic star polymers 7 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Such interests are justified by the potential applications of spinel-ferrites that involve spintronic and magnetic resonance imaging (MRI), gas sensors, magnetic recording, medical diagnostics, antibacterial agents and self-controlled magnetic hyperthermia [5,6,7,8]. Thanks to the spinel-ferrites’ exceptional electric and magnetic properties, they are promising significant future advancements in Lithium-Ion batteries, microwave electronics and catalysis [9,10,11]. The coercivity, remanent magnetization, saturation magnetization and anisotropy constant of the spinel-ferrites are found at the basis of many other applications [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that continuous oxidation and self‐polymerization of dopamine in basic solution (pH 8.5) results in thin layers of polydopamine that adhere to the olivine particles, forming a uniform coating layer . This approach has also been applied to improve the conductivity and cycling stability of other materials, such as SnO 2 , ZnFe 2 O 4 and Li 4 Ti 5 O 12 lithium‐ion battery anode materials, LiMn 2 O 4 , Li[Li 0.2 Ni 0.16 Mn 0.56 Co 0.08 ]O 2 and Na 3 V 2 O 2 (PO 4 ) 2 F cathode materials. Though the reported data suggest some improvement of the battery performance due to the modification of the material surface with a uniform carbon layer, no information is available on the effect of the layer thickness on the rate‐capability of the cathode material, which is determined by the values of ionic diffusion coefficients, charge transfer rate constants and nucleation barrier heights for materials, which undergo nucleation‐controlled phase transitions …”
Section: Introductionmentioning
confidence: 99%